If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(a + b) + 2(2 + b) = 0 (a * 2 + b * 2) + 2(2 + b) = 0 (2a + 2b) + 2(2 + b) = 0 2a + 2b + (2 * 2 + b * 2) = 0 2a + 2b + (4 + 2b) = 0 Reorder the terms: 4 + 2a + 2b + 2b = 0 Combine like terms: 2b + 2b = 4b 4 + 2a + 4b = 0 Solving 4 + 2a + 4b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + 2a + -4 + 4b = 0 + -4 Reorder the terms: 4 + -4 + 2a + 4b = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2a + 4b = 0 + -4 2a + 4b = 0 + -4 Combine like terms: 0 + -4 = -4 2a + 4b = -4 Add '-4b' to each side of the equation. 2a + 4b + -4b = -4 + -4b Combine like terms: 4b + -4b = 0 2a + 0 = -4 + -4b 2a = -4 + -4b Divide each side by '2'. a = -2 + -2b Simplifying a = -2 + -2b
| 3/4-1/2=3/4-2/4 | | -(-7+5s)=-8s+4 | | (7k^3/n)^-2 | | x^4-2y=c | | 5(3k-3)=105 | | (2k^5/n^2)^-3 | | 2(4a+5)=26 | | 13=2(w-14) | | x^(1/2)=.16 | | 23+3m=36 | | -4-2y+x=0 | | 27+13x=45+4x | | 8x+56=15x+21 | | x^2-2(2k-3)x+3k^2+5k+9=0 | | 12x=135-25y | | 2x-1+4x-8=5-9 | | 63+2x=9x+35 | | 72+4x=45+13x | | 2x+3y=4x | | 6x+12=9x+9 | | 18m/14mn | | 35+13x=42+6x | | 9x+10y=75 | | 12+12x=18+6x | | 4+7x=9x+2 | | 1+8x=8+7x | | 3x+21=14+10x | | 10+9x=30+4x | | 72+1x=10x+36 | | 4x+56=12x+16 | | 72+3x=12x+18 | | 27+5x=13x+18 |